Training On Organic Waste Processing Through Maggot Utilization In The Bulu Cindea Village Community, Bungoro Sub-District, Pangkep District: Pelatihan Pengolahan Sampah Organik Melalui Pemanfaatkan Maggot Pada Masyarakat Desa Bulu Cindea, Kecamatan Bungoro, Kabupaten Pangkep - Natsir, Muh. Fajaruddin; Amqam, Hasnawati; Rasyid, Basir (Yayasan Ahmar Cendekia Indonesia, 2023)
The problem of waste is experienced in many places, including Desa Bulu Cindea, Bungoro District, Pangkep Regency. Many people in Bungoro District dispose of their waste indiscriminately, which negatively impacts the environment. Additionally, there are many people in Bungoro District who rely on fish farming and, therefore, require fish feed. The objective of this activity is to address the issue of organic waste through the utilization of maggots. The community engagement activities involve training sessions and focus group discussions (FGD), with 19 participants from Desa Bulu Cindea, Bungoro District, Pangkep Regency. Evaluations of pre-post tests revealed an improvement in participants' knowledge before and after the training. The percentage of insufficient knowledge decreased from 94.1% to 7.6% after the training, while sufficient knowledge increased from 5.9% to 64.7%, and good knowledge increased from 0% to 17.6%. We hope that the government of Desa Bulu Cindea, Bungoro District, Pangkep Regency, as well as the local community, can effectively manage their organic waste by utilizing maggots, thereby enabling the community to use maggots as an alternative feed for fish farming and livestock. Abstrak Permasalahan sampah merupakan masalah yang dialami dibanyak tempat termasuk juga Desa Bulu Cindea, Kecamatan Bungoro, Kabupaten Pangkep. Masyarakat di Kecamatan Bungoro banyak yang membuang sampahnya sembarangan. Sampah ini tentunya akan berdampak buruk bagi lingkungan. Selain itu banyak masyarakat yang pekerjaannya adalah petani tambak yang tentunya membutuhkan pakan ikan. Tujuan dari kegiatan ini adalah untuk mengatasi masalah sampah organik melalui pemanfaatan maggot. Metode kegiatan pengabdian masyarakat berupa pelatihan dan FGD terhadap 19 orang masyarakat Desa Bulu Cindea, Kecamatan Bungoro Kabupaten Pangkep. Dari hasil evaluasi pre post test, didapatkan bahwa terjadi peningkatan pengetahuan peserta sebelum dan setelah pelatihan. Persentase pengetahuan yang kurang, yang sebelumnya 94,1 %, setelah diberikan pelatihan berkurang menjadi 7,6 %, sedangkan pengetahuan cukup meningkat dari 5,9 % menjadi 64,7 % dan pengetahuan yang baik dari 0 % menjadi 17,6 %. Diharapkan kepada pemerintah Desa dan masyarakat Bulu Cindea, Kecamatan Bungoro Kabupaten Pangkep agar dapat mengolah sampah organiknya dengan memanfaatkan maggot, sehingga masyarakat dapat memanfaatkan maggot sebagai pakan alternatif untuk tambak ikan dan ternak mereka.